Temporal Competence of Future Public Sector Managers - Hoi , Nataliia; Zhuk , Olha; Drabchuk , Nataliia; Melnychuk , Vasyl (Insight: the psychological dimensions of society, 2025)
The aim of the study is to investigate the temporal competence of future public sector managers in the context of professional formation and development. Methods. The sample consisted of students at three levels (n = 112) who were enrolled in the academic field 281 “Public Management and Administration” at Vasyl Stefanyk Precarpathian National University (Ivano-Frankivsk, Ukraine). Respondents aged 18 to 44 years participated in both full-time and part-time study formats (M = 25.12; SD = 5.03; Me = 25.00). A valid, reliable, and representative set of instruments was applied: “Personal Orientation Inventory” by E. Shostrom (1964); “Time Perspective Inventory” (Zimbardo & Boyd, 1999; adaptation by O. Senyk, 2012); and “Dispositional Characteristic of Personal Self-Development” (Kuzikova, 2017). Results. Unexpectedly significant correlations were found (p < .001) between high levels of temporal competence and the parameters of time perspective, dispositional development, and the level of educational and professional preparation. It was explained that temporal competence reflects how much an individual lives in the present, whether they exhibit a “delayed life syndrome”, and whether they are stuck in the past. It was noted that a balanced time perspective (Group 1) significantly surpassed Group 2 – respondents with time de-centering – in terms of temporal competence, dispositional development, and the level of educational and professional preparation (p < .001). Discussion and Conclusions. It was argued that the temporal competence of future public sector managers is the ability to rationally plan and utilize working time, adequately assess the complexity of tasks, and be prepared to construct a relevant program for achieving goals within a temporal continuum while accurately determining time expenditures. Temporal competence, which operates within the dimensions of an optimal time perspective profile, is a crucial component in the educational and professional activities of future public sector managers. The empirical findings presented hold scientific novelty and are of significance to specialists in administrative management.